GC-MS Analysis of Potentially Volatile Compounds of Pleurotus ostreatus Polar Extract: In vitro Antimicrobial, Cytotoxic, Immunomodulatory, and Antioxidant Activities - Hamad, Doaa; El-Sayed, Heba; Ahmed, Wafaa; Sonbol, Hana; Ramadan, Mohammed Abdel Halim (Frontiers in Microbiology, 2022)
One strategy to manage resistant pathogens and develop potential anticancer drugs is the search for new, promising, and cost-effective medicinal benefits in the field of bioactive metabolites derived from mushrooms. In the current study, Egyptian cultivated Pleurotus ostreatus fruiting bodies polar extract (PoPE) was prepared to evaluate its antimicrobial activities as well as its cytotoxic effect on various cancer cell lines. The extract was characterized by its phenolic and flavonoid content. The phenolics and flavonoids of PoPE were 6.94 mg/g and 0.15 mg/g, respectively. P. ostreatus polar extract showed potent antimicrobial activity against four pathogens, including Candida albicans, Staphylococcus aureus, Micrococcus luteus, and Escherichia coli. PoPE was found to inhibit Fusarium oxysporum (47%), Fusarium solani (28%) as well as Rhizoctonia solani (21%). PoPE was found to be 13 times more selective and toxic to MCF-7 cells than Vero normal cells, with the lowest IC50 value (4.5 g/mL), so they were selected to examine the potential cytotoxic effects of PoPE. In MCF-7 cells, PoPE appeared to promote cell cycle arrest in the sub-G1 stage, as well as apoptosis. It significantly increased TNF- α production while decreasing IL-6 levels. PoPE's total antioxidant capacity, lipid peroxide, and glutathione reductase activity were recorded 0.14±0.02 mM/L, 15.60±0.015 nmol/mL, and 9.50±1.30 U/L, respectively. The existence of different bioactive metabolites was investigated via GC–MS, which confirmed the presence of 15 compounds with well-known biological activity.